What is the irrigation potential for Africa? A combined biophysical and socioeconomic approach - You, Liangzhi; Ringler, Claudia; Nelson, Gerald C.; Wood-Sichra, Ulrike; Robertson, Richard D.; Wood, Stanley; Guo, Zhe; Zhu, Tingju; Sun, Yan (International Food Policy Research Institute, 2010)
Although irrigation in Africa has the potential to boost agricultural productivities by at least 50 percent, food production on the continent is almost entirely rainfed. The area equipped for irrigation, currently slightly more than 13 million hectares, makes up just 6 percent of the total cultivated area. Eighty-five percent of Africa's poor live in rural areas and mostly depend on agriculture for their livelihoods. As a result, agricultural development is key to ending poverty on the continent. Many development organizations have recently proposed to significantly increase investments in irrigation in the region. However, the potential for irrigation investments in Africa is highly dependent upon geographic, hydrologic, agronomic, and economic factors that need to be taken into account when assessing the long-term viability and sustainability of planned projects. This paper analyzes large, dam-based and small-scale irrigation investment needs in Africa based on agronomic, hydrologic, and economic factors. This type of analysis can guide country- and local-level assessment of irrigation potential, which will be important to agricultural and economic development in Africa.